Mandailing and Javanese Cultural Communication in Preserving Interethnic Harmony in Tanjung Ale from an Islamic Perspective - Masnawari Harahap; Mailin Mailin (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
Tanjung Ale Village reflects the harmony between the Mandailing and Javanese ethnic groups through intercultural communication grounded in Islamic values, local customs, and traditions, which collectively strengthen the social cohesion of the local community. This study aims to analyze the role of intercultural communication between the Mandailing and Javanese communities in maintaining social harmony in Tanjung Ale Village, with Islamic values serving as the primary foundation. As a multicultural society inhabited by two major ethnic groups, intercultural communication is a crucial element in preserving social harmony. This research employs a descriptive qualitative approach, utilizing observation, interviews, documentation, and triangulation methods. Data analysis is conducted through data reduction, data presentation, and conclusion drawing. Both verbal and non-verbal communication in Mandailing and Javanese traditions reflect values of togetherness, respect, and spirituality. The integration of cultural symbols, deliberative consensus (musyawarah), and Islamic values reinforces interethnic harmony through traditional wedding ceremonies. Islamic teachings influence community attitudes by promoting values of tolerance, respect, and brotherhood. Practices of religious moderation and intercultural communication strengthen social cohesion, encouraging mutual cooperation, open dialogue, and the preservation of harmony amid cultural diversity. Islamic teachings recognize ethnic diversity as a blessing from God and emphasize the importance of unity while avoiding division. Intercultural communication and fair conflict resolution are regarded as forms of religious devotion that contribute to social harmony and communal well-being. Conclusion: The intercultural communication between the Mandailing and Javanese, when integrated with Islamic values, reinforces tolerance, brotherhood, and religious moderation, thereby fostering sustainable social harmony and cohesion.